The Effect of Feeding Red Ginger (Zingiber officinale Rosc) as Phytobiotic on Broiler Slaughter Weight and Meat Quality - Herawati; Marjuki (International Journal of Poultry Science, 2011)
The research aimed to evaluate the potency of Red Ginger (Zingiber officinale Rosc) as a source of phytobiotic in the ration to increase physical quality of broiler meat. Two hundred of five days old broiler chickens were plotted into five different groups and each group was further divided into five sub-groups. Each group was given different rations, i.e.: R-0 (control ration without red ginger added); R-0.5, R-1.0, R-1.5, and R-2.0% (control ration added with red ginger at level 0.5, 1.0, 1.5, and 2.0% of the ration, respectively). All rations were designed as iso-protein ration with CP content of 21.0-23.0%, iso-caloric with energy content of 3150 kcal ME/kg, Ca 1.0%, and P 0.5%. The broilers were raised for 5 weeks. After five weeks all broilers were slaughtered and weighed to get data for carcass quality (slaughter weight, carcass weight, carcass percentage, fat weight and fat percentage) and the data of meat physical quality including pH, tenderness, water holding capacity (WHC), cooking loss (CL). The collected data were subjected to analysis of One Way Classification of Completely Randomized Design (CRD) and Duncan’s New Multiple Range Test (DMRT). The result showed that broilers given ration with red ginger showed significantly higher slaughter weight (P